Deformation of food powders by nanoindentation - Yusof, Yus Aniza; Smith, A. C.; Briscoe, B. J. (Federation of Engineering Institutions of Islamic Countries, 2006)
Nanoindentation is a test where an indenter induces a localised deformation into a sample surface to determine material properties such as hardness and modulus of elasticity at nanometer scale. The indentation technique to be used in this study is called a depth indentation test. The technique is based on the recording of the applied force as a function of penetration depth during the loading and unloading processes. In this paper, the compacted fine maize, coarse maize, and Avicel were investigated upon nanoindentation. This test is carried out so that the deformability of the food powders, which has viscoelastic characteristic may be understood better.It was found that Avicel powder may form a more strong and coherent junction compared to maize powders. Direct evidence may be seen from the measurements of hardness and modulus of elasticity of the powders.